PENGARUH KOMPENSASI FINANSIAL DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN HUMAN RESOURCE - Parmanasari, Embun; Suryani, Emma (Tirtayasa Ekonomika, 2018)
This study aims to determine the effect of financial compensation and career development on turnover intention with job satisfaction as intervening variable. In this research the method used is descriptive and causal method. Data collection techniques used questionnaires with interval scale measurements. Using a saturated sample and obtained 30 respondents using quantitative data analysis methods. From result of calculation of SPSS v.20, result of research with significance level of 0,05% got conclusion: (1) financial compensation have positive and significant effect to job satisfaction obtained t count > t table (5,303 > 1,701) with sig value < 0.05 (0.00 < 0.05) (2) career development has a positive and significant influence on job satisfaction obtained t count > t table (2.118 > 1.701) with sig < 0.05 (0.044 < 0.05) (3) financial compensation has a non-significant positive effect on intention turnover obtained t count < t table (1.669 < 1.701) with sig value > 0.05 (0.107 > 0.05) (4) career development has a negative and significant influence on intention turnover obtained        –t count  > -t table (-2.094 > -1701) with value sig < 0.05 (0.046 < 0.05) (5) job satisfaction has a negative and significant influence on intention turnover obtained  -t count > -t table (-2.439 > -1.701) (6) job satisfaction does not mediate compensation relationship (7) job satisfaction does not mediate the career development relationship to turnover intention and the effect is not significantly obtained -t count < -t table (-1.189 < -1.701)